Impulsif Buying Tendency sebagai Dampak dari Stimulus Lingkungan Toko dengan Pemediasi Emosi Positif (Studi pada Matahari Department Store di Thamrin Plaza Medan) - Dhika Rara Ayu (Universitas Harapan Medan, 2020)
This research is based on the notion that the tendency of widespread shopping behavior that occurs in the market so that it becomes an important point in marketing. Impulsive buying behavior is a challenge for business people where they are required to create emotionally attractive interests such as attracting consumers to buy and consume the product. Therefore this researcher aims to describe Impulsive Buying Tendency as the impact of the Store Environment Stimulus by mediating the Positive Emotions of studies at Matahari Department Store in Thamrin Plaza Medan. This research was conducted at Thamrin Plaza Medan, on Jalan M.H.Thamrin, Sei Rengas II, Medan. This research uses quantitative research methods.The population of Matahari Department Store's consumer research population is unknown. The sample in this study amounted to 100 people. Data collection instruments using questionnaires that were assessed on a Likert scale, each of which was tested and met the requirements of reliability and reliability. Data analysis uses Statistical Package Social Sciences (SPSS).The results obtained and at the same time conclude this study include that impulsive buying has a significant effect on the store environment, impulsive buying has a significant effect on positive emotions, positive emotions have a significant effect on the store environment, and impulsive buying affects the store environment through positive emotions as a mediating variable . Thus it can be concluded that the hypothesis of this study can be accepted.